A Reinforcement of Religious Understanding of High School Students on Radicalism During Pandemic - Raharjo; Lutfiyah, Lutfiyah; Muthohar, Sofa; Mutohar, Ahmad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Terrorism as a manifestation of radicalism seems to arise and sink. The segment of radicalism is the teenagers at the high school level. This because they are the transition from childhood to adulthood. The positive thinking mindset is seen with clarity of thought and brings the pandemic phenomenon as resilience to counteract radical thought patterns. The purpose of this study is to make the pandemic period a momentum for strengthening students' religious understanding as a counter to radicalism. This study is qualitative research with a content analysis approach to social media content. The results show that there are 5 (five) ways to strengthen religious understanding as an effort to deradicalize high school students, namely: (1) Fostering logical thinking patterns wrapped in religion (science spiritualism), (2) Presentation of neutral readings so that their direction of reasoning is organized, balanced between thoughts state and religion, (3) Cultivating balance and moderate attitudes, (4) Modelling attitudes and behaviours that are easy to imitate from teachers and education leaders, (5) optimizing the role of parents to assist students in distance learning patterns, learning from home, or online learning.